Mycosis Fungoides - Sayal S K; Malik A K; Sanghi S; Chatterjee T; Prasad G K (Wolters Kluwer Medknow Publications, 2001)
A case of Mycosis Fungoides showing typical clinical and histopathological features responding to PUVASOL therapy.